2018
DOI: 10.1016/j.foodchem.2018.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology to optimize supercritical carbon dioxide/co-solvent extraction of brown onion skin by-product as source of nutraceutical compounds

Abstract: Food industry produces a large amount of onion wastes. Due to the high amount of bioactive compounds in onion by-products an idea for their reuse, could be use them as source of high-value functional and health ingredients. In this study, outer dry layers of coppery onion "Ramata di Montoro" were used as source of bioactive compounds. Firstly, the chemical profile of secondary metabolites of exhaustive extract, obtained by ultrasound assisted extraction was established by UHPLC-UV-HRMS/MS analysis. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 36 publications
8
53
0
Order By: Relevance
“…In another study, the outer layer of red onion showed the highest antioxidants and antioxidant activities than the purple, white, and green varieties of onion, as determined by in vitro antioxidant and free radical scavenging activities (Prakash et al, 2007). In a recent study, Campone et al (2018) optimized the extraction of phenolic compounds from brown onion. They compared ultrasound-assisted extraction and supercritical carbon dioxide/cosolvent extraction and found that phenolics from the latter method showed better antioxidant activity.…”
Section: Onionsmentioning
confidence: 99%
“…In another study, the outer layer of red onion showed the highest antioxidants and antioxidant activities than the purple, white, and green varieties of onion, as determined by in vitro antioxidant and free radical scavenging activities (Prakash et al, 2007). In a recent study, Campone et al (2018) optimized the extraction of phenolic compounds from brown onion. They compared ultrasound-assisted extraction and supercritical carbon dioxide/cosolvent extraction and found that phenolics from the latter method showed better antioxidant activity.…”
Section: Onionsmentioning
confidence: 99%
“…e DPPH°assay was used to evaluate the antioxidant activity of all extracts; the parameters used were previously described by Brand-Williams et al [39] with some modification in order to be performed in 96-well microplate. e experimental conditions were reported by Campone et al [40] and were as follows: 5 μL of XAD extracts in the range of 1-15 mg•mL − 1 was mixed to 195 μL of DPPH°standard solution at concentration of 120 μM, at room temperature, and protected from light. After 90 min, the absorbance was read at 515 nm using a Multiskan Go spectrophotometer ( ermo Fischer Scientific).…”
Section: Radical Dpph Scavenging Activitymentioning
confidence: 99%
“…The reuse of onion by-products in high-value functional and healthy ingredients may offer the opportunity to valorize these low-cost food by-products in economically interesting perspectives, exploiting their potential applications in functional foods, supplements, cosmetics, and nutraceutical products. This comes in a context in which consumers increasingly refuse synthetic food supplements, expressing their preferences for ingredients from natural sources with beneficial effects on health [ 7 , 8 ]. It has been reported that the major by-products resulting from the industrial peeling of onion bulbs are dried skin, the outer two fleshy leaves, and the top and bottom bulbs, which are not edible and are removed before processing [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the major by-products resulting from the industrial peeling of onion bulbs are dried skin, the outer two fleshy leaves, and the top and bottom bulbs, which are not edible and are removed before processing [ 9 ]. Onion wastes, due to a rapid phytopathogens growth and to their strong unique smell, are not suitable for fodder or landfill disposal [ 7 ]. Therefore, the development of strategies to valorize these by-products is immediately required, with benefits for both processors and consumers, while significantly reducing the negative impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation